What Photographs Do The making and remaking of museum cultures - Edwards, Elizabeth; Ravilious, Ella (UCL Press, 2022)
What are photographs 'doing' in museums? Why are some photographs valued and others not? Why are some photographic practices visible and not others? What value systems and hierarchies do they reflect? What Photographs Do explores how museums are defined through their photographic practices. It focuses not on formal collections of photographs as accessioned objects, be they 'fine art' or 'archival', but on what might be termed 'non-collections': the huge number of photographs that are integral to the workings of museums yet 'invisible', existing outside the structures of 'the collection'. These photographs, however, raise complex and ambiguous questions about the ways in which such accumulations of photographs create the values, hierarchies, histories and knowledge-systems, through multiple, folded and overlapping layers that might be described as the museum's ecosystem. These photographic dynamics are studied through the prism of the Victoria and Albert Museum, London, an institution with over 150 years' engagement with photography's multifaceted uses and existences in the museum. The book differs from more usual approaches to museum studies in that it presents not only formal essays but short 'auto-ethnographic' interventions from museum practitioners, from studio photographers and image managers to conservators and non-photographic curators, who address the significance of both historical and contemporary practices of photography in their work. As such this book offers an extensive and unique range of accounts of what photographs 'do' in museums, expanding the critical discourse of both photography and museums.